Faculty Perspectives on the Importance and Challenges of Conducting Educational Research in Higher Education Institutions - Al Abdulghafour, Mahammad; Al Sahel, Rashed; Bokubar, Anwar; Alhashem, Fatimah (Journal of Education Culture and Society, 2025)
Aim. This study explores faculty perceptions of the importance of educational research and the challenges they face in conducting it at Kuwait University’s College of Education. While educational research is widely regarded as a critical tool for advancing teaching practices, curriculum development, and policymaking, significant barriers limit its effective implementation.Methods. A descriptive survey design was employed to collect data from 82 faculty members across various academic ranks and departments. The questionnaire included items measuring the perceived importance of educational research and the obstacles to its conduct.Results. The findings revealed that faculty members highly value educational research, with 98% agreeing that it contributes to reconstructing educational curricula and 93.9% recognising its role in developing educational processes. The study also identified several critical barriers to faculty engagement in research, including a lack of supporting research personnel (78%), weak institutional incentives (67%), and heavy teaching loads (69.5%). These findings are consistent with previous studies that highlight the need for better institutional support, adequate research infrastructure, and balanced workload management to enhance faculty research productivity. Additionally, nearly 60% of faculty members perceived educational research as being too theoretical and disconnected from practical application, suggesting a need for more practice-oriented and collaborative research models.Conclusions. The study concludes that while faculty members are aware of the importance of educational research, significant systemic challenges must be addressed to foster a more conducive research environment. Recommendations for practice include strengthening research support structures, revising incentive policies, promoting collaborative research efforts, and investing in faculty development programs.